Weak and False Hadits in Learning Book of Qur’an and Hadits at Islamic Schools - Wajidi Sayadi (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The research goals are to answer some questions related to the materials and the quality of hadits which are taught in Madrasah Ibtidaiyah (Islamic Elementary School) and Madrasah Tsanawiyah (Islamic Junior high School). The text book of Quran and Hadits both schools are based on the curriculum 1988, it refers to the regulation of Ministry of Religious Affairs no 2/2008. The subject of Quran and Hadits is part of the subject of Religious Education in Madrasah Ibtidaiyah and Madrash Tsanawiyah, and the purpose is to enable students to understand Quran and Hadist as the sources of Islamic teaching. The subject of hadits is the hadits which really refer to Prophet Muhammad with the valid (shahih) chain of hadits narators. There are nine textbooks of Quran and Hadits that are learned depending on the numbers of class. There are 31 hadits as main materials to be discussed and other hadits as supporting materials. The data (hadits) is analyzed using criticts of hadits. The finding of the research reveals that not all materials of hadits taught in madrasah are valid (sahih), some hadits are very poor (weak), and its authenticity is doubtful and even some hadits are false (not authentic).